Impact of seasonal hydrological variation on tropical fish assemblages: abrupt shift following an extreme flood event. Issue 12 (1st December 2020) - Chea, Ratha; Pool, Thomas K.; Chevalier, Mathieu; Ngor, Pengbun; So, Nam; Winemiller, Kirk O.; Lek, Sovan; Grenouillet, Gaël
Abstract: Pulsing hydrology is a major factor affecting fish communities in tropical river‐floodplain ecosystems. Species responses to flow alteration are however poorly understood and are thus difficult to predict. Here, we investigated temporal changes in fish community structure (taxonomic and functional) in the Tonle Sap Lake, a floodplain ecosystem in Cambodia that supports the world largest inland fisheries and a UNESCO biosphere reserve. Fish catches were monitored daily at five locations around the lake between 2012 and 2015, with 53 species obtained over the course of the field study. Nine fish traits were recorded and used to characterize the functional composition of fish communities. Temporal changes in functional community structure in response to hydrological variation were assessed using multiple co‐inertia analysis (MCOA) and cross‐correlation function (CCF) approaches. Analyses revealed an abrupt shift in functional structure following extreme flood events in 2013 that included a marked decrease in large‐bodied fish at high trophic levels. Also observed were seasonal changes in the relative abundance of life‐history strategies, feeding habits, and accessory respiratory adaptations. Black fish (species that are relatively sedentary with an equilibrium‐type life‐history strategy) dominated during low‐water periods, whereas white fish (migratory species with opportunistic or periodic life‐history strategies) were dominant during high‐water periods. Dynamics of local assemblage structure were fairly synchronous spatially and were independent of the distance between locations. Species responses to the peak flood pulse were estimated to lag 1–2 months. Findings from this study indicate that management of fisheries resources in the Tonle Sap Lake should consider differential responses of species to hydrology as a function of life‐history strategies and other functional traits as well as factors that may influence time lags in population and community changes to extreme flow events.